2020
DOI: 10.1021/acs.langmuir.0c00579
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Generation of Nitric Oxide from Poly(ε-caprolactone)/Phosphobetainized Keratin Mats for a Vascular Tissue Engineering Scaffold

Abstract: Tissue-engineered vascular graft (TEVG) is a promising alternative to meet the clinical demand of organ shortages. Herein, human hair keratin was extracted by the reduction method, followed by modification with zwitterionic 2-methacryloyloxyethyl phosphorylcholine (MPC) through thiol–Michael addition to improve blood clotting nature. Then, phosphobetainized keratin (PK) was coelectrospun with poly­(ε-caprolactone) (PCL) to afford PCL/PK mats with a ratio of 7:3. The surface morphology, chemical structure, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
(75 reference statements)
0
14
0
Order By: Relevance
“…Together with APTT, PT and TT were used to establish the procoagulant and anticoagulation activities of the prepared fiber scaffolds. 42 Compared with the P/G scaffold, APTT for the P/G-SA scaffold was prolonged (Figure 7B) because of the quick release of heparin. The PT results for the four scaffolds of P/G, P/G-CDI, P/G-CG, and P/G-HA were similar to those of the control samples (Figure 7C).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Together with APTT, PT and TT were used to establish the procoagulant and anticoagulation activities of the prepared fiber scaffolds. 42 Compared with the P/G scaffold, APTT for the P/G-SA scaffold was prolonged (Figure 7B) because of the quick release of heparin. The PT results for the four scaffolds of P/G, P/G-CDI, P/G-CG, and P/G-HA were similar to those of the control samples (Figure 7C).…”
Section: Resultsmentioning
confidence: 98%
“…We studied the coagulation time of different PLGA/GelMA scaffolds by APTT, PT, and TT, and the protein adsorption behavior by the adsorbed amount of FIB. Together with APTT, PT and TT were used to establish the procoagulant and anticoagulation activities of the prepared fiber scaffolds . Compared with the P/G scaffold, APTT for the P/G-SA scaffold was prolonged (Figure B) because of the quick release of heparin.…”
Section: Resultsmentioning
confidence: 99%
“… 149 Similarly, keratin-doped poly(ε-caprolactone) vascular tubes exhibited selective function that facilitated EC repopulation while preventing SMC growth thanks to the NO production by catalyzing S-nitrosoglutathione available in the blood. 150 , 151 In another attempt to mimic the endothelium that protects the vessel wall from the platelet attachment, a glycocalyx-like hyaluronic acid coating on the decellularized TEVG lumen reduced thrombus formation. 152 Other approaches to prevent thrombosis in small-caliber grafts include in situ endothelial seeding into the graft lumen, 153 coating of the lumen with agents to promote endothelialization via circulating endothelial progenitor cells or migrating ECs from the anastomosis regions, 154 and coimmobilization of the ACH11 antithrombotic peptide and CAG cell-adhesive peptide to prevent platelet activation and facilitate EC adhesion at the same time (Figure 3 ).…”
Section: Current and Future Research Avenuesmentioning
confidence: 99%
“…Shen et al found that disulfide in keratin could be decomposed into thiol by GSH, catalyzing GSNO to produce NO. [132] Human hair keratin was extracted through thiol-Michael addition and was modified with 2-methacryloyloxyethyl phosphorylcholine (MPC) to attain blood anticoagulant activity. Finally, the phosphobetainized keratin and PCL were co-electrospun to generate PCL/PK nanofibrous mats.…”
Section: 𝛼-Cd-conjugated No Prodrug (𝛼-Cd-no) and Ce6 (𝛼-Cd-ce6mentioning
confidence: 99%